Associations of BRAP polymorphisms with the risk of alcohol dependence and scores on the Alcohol Use Disorders Identification Test - Kim JW (Dove Medical Press, 2018)
Jee Wook Kim,1,2 Young Min Choe,1,2 Joong-Gon Shin,3 Byung Lae Park,4 Hyung-Doo Shin,3,4 Ihn-Geun Choi,2,5 Boung Chul Lee2,6 1Department of Neuropsychiatry, Hallym University Dongtan Sacred Heart Hospital, Hwaseong, Gyeonggi Province, Republic of Korea; 2Department of Psychiatry, Hallym University College of Medicine, Chuncheon, Republic of Korea; 3Department of Life Science, Sogang University, Seoul, Republic of Korea; 4Department of Genetic Epidemiology, SNP Genetics, Inc., Seoul, Republic of Korea; 5Department of Neuropsychiatry, Hallym University Kangnam Sacred Heart Hospital, Seoul, Republic of Korea; 6Department of Neuropsychiatry, Hallym University Hangang Sacred Heart Hospital, Seoul, Republic of Korea Background: Alcohol dependence (AD) is a common disorder that is influenced by genetic as well as environmental factors. A previous genome-wide association study (GWAS) of the Korean population performed by our research group identified a number of genes, including BRCA1-associated protein (BRAP) and protein arginine methyltransferase 8 (PRMT8), as novel genetic markers of AD. Methods: The present investigation was a fine-mapping follow-up study of 459 AD and 455 non-AD subjects of Korean descent to determine the associations between BRAP and PRMT8 polymorphisms and AD. The Alcohol Use Disorders Identification Test (AUDIT) was administered to screen for the degree of AD risk in the subjects and 58 genetic variants, 5 for BRAP and 53 for PRMT8, were genotyped for subsequent association analyses. Results: In the present case–control analysis, BRAP rs3782886 showed the most significant association signal with a risk of AD (P=1.29×10-16, Pcorr =7.74×10-16, OR =0.19). There were also significant differences in the overall and subcategory scores for the BRAP genetic variants, including rs3782886 (P=9.94×10-31, Pcorr =5.96×10-30 at rs3782886 for the overall AUDIT score). However, the genetic effects of PRMT8 polymorphisms observed in our previous GWAS were not replicated in the present study (minimum P=0.0005, Pcorr >0.05, OR =0.30 at rs4766139 in the recessive model). Furthermore, the single-nucleotide polymorphisms of PRMT8 were not associated with the overall and subcategory AUDIT scores. Conclusion: The present findings suggest that the genetic variants of BRAP may contribute to a predisposition for an alcohol use disorder. Keywords: alcohol dependence, AUDIT, genome-wide association study, single-nucleotide polymorphism, BRAP